Bees of the genus Colletes Latreille 1802 of the Asian part of Russia, with keys to species (Hymenoptera: Apoidea: Colletidae) - Kuhlmann, Michael; Yu. Proshchalykin, Maxim (Zootaxa, 2011)
For the Asian part of Russia 27 species of the bee genus Colletes are recorded. Colletes ravulus Noskiewicz 1936 is recorded for the first time from Russia. Colletes fodiens (Fourcroy 1785), C. similis Schenck 1853, and C. marginatus Smith 1846 are newly recorded from the Asian part of Russia. Colletes kirgisica Radoszkowski 1867 syn. nov. (= Colletes fodiens kirgisicus Radoszkowski 1867) and Colletes fodiens hispanicus Noskiewicz 1936 syn. nov. are recognized as synonyms of Colletes fodiens (Fourcroy 1785). The female of C. ravulus is here described for the first time. Additionally C. edentuloides Kuhlmann sp. nov. is described from neighbouring Mongolia as it hitherto has been thought to be the female of C. ravulus. Illustrated keys to males and females of all species known from the Asian part of Russia are provided.